2019
DOI: 10.1038/s41598-018-37853-4
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the robust superhydrophobic silicon textures with stable photodetection properties

Abstract: Surface hydrophobicity of silicon with sound durability under mechanical abrasion is highly desirable for practical needs. However, the reported micro-pyramid/nanowires structures suffer from the saturation characteristics of contact angle at around 132 degree, which impede the promotions toward reaching the state of superhydrophobicity. The present study focuses on the realization of two-scale silicon hierarchical structures prepared with the facile, rapid and large-area capable chemical etching methods witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…4. It has been reported that the measured contact angle was correlated with the roughness of nanostructures according to the equation shown below [24,25],…”
Section: Resultsmentioning
confidence: 99%
“…4. It has been reported that the measured contact angle was correlated with the roughness of nanostructures according to the equation shown below [24,25],…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the use of this Cassie model modified in accordance with the surface geometry can be effective in the study of non-stochastic structures obtained by laser processing [28], anisotropic chemical etching of the silicon surface [29], etc.…”
Section: Determining the Distribution Of The Liquid Contact Surfacementioning
confidence: 99%